Exploring the additive compatibility and tribological behavior of regular and high oleic soybean oil - Bhowmik, Piash; Sharma, Brajendra K.; Sarker, Majher I.; Mainali, Kalidas; Wang, Yachao; Tang, Clement; Roy, Sougata (Frontiers in Mechanical Engineering, 2024)
As the demand for biobased lubricating oils continues to rise, there is a growing focus on exploring diverse oil types. Particularly noteworthy is the surge in demand for high oleic oils, which offer enhanced stability, and a richer oleic acid content compared to their regular oil counterparts. However, the performance of high oleic soybean oil (HOSO) with additives compared to regular soybean oil (RSO), remains unclear. This study is focused on revealing the compatibility of both regular soybean oil (RSO) and high oleic soybean oil (HOSO) with select antiwear and antioxidant additives, specifically zinc dialkyl dithiophosphate (ZDDP), and zinc dialkyl dithiocarbamate (ZDDC) combined with antimony dialkyldithiocarbamate (ADDC), along with a comparative performance analysis of these additives. Reciprocating friction, wear, and electrical contact resistance-based analyses were conducted to evaluate additive compatibility and wear mechanisms at room temperature lubrication conditions. Interestingly, it was observed that for the select additives, the compatibility with regular soybean oil (RSO) was better than that of high oleic soybean oil (HOSO). RSO with additives showed around 28% reduction of wear volume whereas, it was only 8% for HOSO with additives. Additional physiochemical property analyses were conducted on the lubricants to correlate the observed tribological behavior. The worn-out surfaces of the test samples were characterized thoroughly to reveal the dominant wear mechanisms.